2011
DOI: 10.2147/ndt.s20173
|View full text |Cite
|
Sign up to set email alerts
|

Clobazam as an adjunctive therapy in treating seizures associated with Lennox–Gastaut syndrome

Abstract: Lennox–Gastaut syndrome (LGS) is a devastating childhood epilepsy syndrome characterized by the occurrence of multiple types of seizures and cognitive decline. Most children suffer from frequent seizures that are refractory to current medical management. Recent clinical trials have suggested that addition of clobazam may improve the clinical outcome for some LGS patients. Although clobazam has been available for over five decades, it has only recently been approved by the US Food and Drug Administration for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 86 publications
(186 reference statements)
0
2
0
Order By: Relevance
“…95 This is a major requirement to make clobazam TDM a better instrument in the prediction of response and ADRs. Unfortunately, it is not easy to study this issue in a definitive way.…”
Section: Discussionmentioning
confidence: 99%
“…95 This is a major requirement to make clobazam TDM a better instrument in the prediction of response and ADRs. Unfortunately, it is not easy to study this issue in a definitive way.…”
Section: Discussionmentioning
confidence: 99%
“…A review study conducted in 2011 evaluated several studies on the effectiveness of CLB, 10 both prospective and retrospective studies. In pediatric patients with refractory epilepsy, six open-label prospective studies have shown that at least 54%-85% of patients experienced at least a 50% drop in seizure rates ( Table 1 ).…”
Section: The Use Of Clobazam As An Adjunct Therapy In the Treatment Omentioning
confidence: 99%
“…Current treatments for epileptic seizures generally aim to increase inhibition or decrease hyperexcitation in the neurotransmission pathways related to seizure pathogenesis ( 11 , 12 ). However, many AEDs, such as Clobazam, do not show adequate effect in many patients ( 13 ). These AEDs could not work as an intervention to control refractory seizures by targeting different intercellular pathways ( 14 ).…”
Section: Introductionmentioning
confidence: 99%